Functional properties of protein hydrolysates obtained from the pigeon pea (Cajanus cajan) / Najihah Mohd Radzi - Mohd Radzi, Najihah (2015)
Proteins are essential components of the diet for human nutrition as sources of energy and amino acids. Protein hydrolysate is product from by enzymatic conversion of protein into smaller peptides. Pigeon pea containing a high protein and the seeds can be prepared into variety of meals and. There only a few information and studied on the protein hydrolysate and functional properties of the pigeon pea. Several analyses were carried out to analyze the chemical and functional properties of the protein hydrolysate obtained from the pigeon pea. The degree of hydrolysis produced by pigeon pea hydrolysate in presence of 5% flavourzyme was 12.44% and in presence of 5% alcalase was 14.53%. The protein solubility was higher at pH 6 and 7 and minimum solubility at pH 4 for both of enzyme substrate. Pigeon pea hydrolysate in presence of 5% flavourzyme a better in water and oil absorption capacity properties while pigeon pea hydrolysate in presence of 5% alcalcase a better in foam stability and capacity properties. Emulsifying properties for both of samples are higher capacity index at pH 7. It was also found that molecular weight for pigeon pea hydrolysate of 5% flavourzyme detected at the range from 50 kDa to > 0 kDa and pigeon pea hydrolysate in presence of 5% alcalse well be detected at the range from 100 kDa to >10 kDa. Functional properties showed in both of pigeon pea hydrolysate in presented of 5% flavourzyme and 5% alcalase give their potential in food industry.